Conservation tillage and nutrient management effects on productivity and soil carbon sequestration under double cropping of rice in north eastern region of India. (October 2019) - Yadav, Gulab Singh; Lal, Rattan; Meena, Ram Swaroop; Babu, Subhash; Das, Anup; Bhowmik, S.N.; Datta, Mrinmoy; Layak, Jayanta; Saha, Poulami
Highlights: The rice ( Oryza sativa )–rice system (RRS) is principal production system in Asia. Loss of soil carbon and nitrogen pools is declining the productivity of RRS. Intensive tillage and improper nutrient management are reasons of the loss of soil C and N. RT/NT with INM and residue recycling can sequestrate C and N in paddy soils. Cultivation RRS under CA with INM/IPNM and residue recycling could enhance productivity. Abstract: The rice ( Oryza sativa )–rice system (RRS) is the most important agricultural production system, and it provides staple food, income, employment, and livelihoods to millions of farmers in the Indian sub- continent, especially in the eastern and north eastern region (NER) of India. However, soil degradation, due to loss of soil carbon (C) and nitrogen (N) pools, is declining the productivity of RRS and threatening the region's food security. Intensive tillage along with improper residues and nutrient management practices are among the reasons of the loss of soil C and N pools and decline in rice productivity. Therefore, a 3-year (2013-15) field study was conducted to evaluate the effects of tillage, residues and nutrient management practices on productivity, soil C and N sequestration in RRS at the Indian Council of Agricultural Research (ICAR)-Research Complex for the North Eastern Hill (NEH) Region, Lembucherra (52 m, above sea level), Tripura, India. The experiment consisted of five combinations of tillage [conventional tillage (CT), reduced tillage (RT) and no-till (NT)], residue [30% rice residue incorporation (RI) and/or residue retention (RR)] and nutrient management practices [inorganic, organic (FYM-farmyard manure, GLM-green leaf manuring) and biofertilizers] in wet (WR) and dry season rice (DR). Results revealed that RT along with improved plant nutrient management (IPNM) comprising 25% N (20 kg N) through GLM + 60 kg N, 9 kg phosphorus (P), 17 kg potassium (K), 2 kg Boron (B) and 5 kg zinc (Zn) ha −1 through fertilizer + cellulose decomposition microorganism and RR in WR produced significantly higher grain yield (5.15 Mg ha −1 ) as compared to other treatments. However, the DR transplanted under CT + integrated nutrient management (INM) comprising 25% N through FYM and 75% N and remaining P and K (after deducting quantity supplied by FYM) through inorganic fertilizer + RI produced more grain (5.1–5.3 Mg ha −1 ), straw (7.0–7.2 Mg ha −1 ), root (1.3–1.4 Mg ha −1 ) and total biomass (13.4–13.9 Mg ha −1 ) yield than that of the farmers' practice (FP) and other treatment combinations, across the years. The highest system productivity of RRS was recorded under T3 (RT + IPNM + RR in WR and CT + INM + RI in DR). Therefore, the highest biomass, C, and N were also recycled in the system through the same treatment combinations. Soil under T3 had a lower bulk density (ρb ), the highest soil organic carbon (SOC)/N concentration, pool, accumulation, sequestration, C retention efficiency, soil microbial biomass C and dehydrogenase activities than other treatments. A total amount of 1.30 Mg C ha −1 was accumulated under soils of T3 with the rate of SOC sequestration of 427.9 kg ha −1 yr −1 under RRS. Thus, adopting RRS under RT/NT with INM/IPNM and effective residue recycling is recommended for enhancing the system productivity, C and N sequestration in paddy soils of the NER of India.